STUDENTS’ PERCEPTION ON LEARNING READING ONLINE - Melani, Intan Dwi; Eliwarti, Eliwarti; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aimed to know the students’ perception on their learning reading online of the second year students of English study program FKIP Universitas Riau. A descriptive-quantitative approach research design was used to conduct this study. The total number of participants is 119 students from the second semester of English study program, classes 4A, 4B, and 4C in the academic year 2019/2020. The instruments used to collect the data were questionnaires. The questionnaire consisted of 21 statements about students’ perceptions on learning reading online. Google Form is the media to distribute the questionnaire due to the global pandemic of Covid-19. Data were analyzed using descriptive statistics in the form of frequencies and percentages. The results of the study indicate that learning reading online does not cause any effects on reading comprehension because perception on learning reading online is the majority in the medium level. But some facilities when learning reading online help students and make them easier in their learning process. The findings of this research showed that there are advantages on learning reading online; the convenience when they understand the text because of the facilities, save copy paper, clear the screen without bad printing quality, and improve their online translation.Key Words: Students’ Perception, Online Learning, Reading Comprehension